(3GdfaMGJ GdUeOjI hGdaJhMGJ GdbOSjIs ((3eMeO Hf CMeO GdgGja s)
(3ChdgG (B:s
(3GdMeO ddg GdefRg Yf GdMeO hGdKfGA CeG HYO agPg faMGJ UeOjI haJhMGJ bOSjI CXgQgG GdhGQO GdQHGfi hGdehGO GdQMef ai eYGfi GdUdGI hchfgG NjQ ehVhY s
(3BNQgG (B:s
(3TQY GdSdGe ETGQI Edi GdCeGf hGLYdfG ef GdehGdjf dge ai cd MGd ddYGOjf ef YGOGge ai GdeHOC hGdeGd gPG BNQ eG JjSQ ai GdebGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdeLGejYs